Genome-wide identification and expression pattern analysis of the chloride channel gene family in potato (Solanum tuberosum L.) under salt stress - Gong, Huiling; Wang, Hang; Chen, Jie; Dusengemungu, Leonce; Feng, Zaiping (Frontiers in Plant Science, 2025)
IntroductionChloride channel (CLC) proteins are crucial anion channels that play a vital role in plant adaptation to abiotic stresses. Potato (Solanum tuberosum L.) is a major global staple crop; however, the CLC gene family in potato (StCLC) remains poorly characterized, and its specific functions in salt tolerance are unclear. This study aimed to systematically identify and characterize the StCLC gene family and analyze its expression patterns under salt stress.MethodsUsing bioinformatics methods based on the potato genome, transcriptome, and qRT-PCR data, we analyzed the protein structures, physicochemical properties, phylogenetic relationships, gene structures, conserved domains, chromosomal locations, collinearity, GO annotations, and promoter cis-acting elements of StCLC members.ResultsSeven StCLC genes (StCLC1–7) were identified and unevenly distributed across four chromosomes. Based on protein structures and phylogenetic relationships with Arabidopsis thaliana CLCs, the seven StCLCs were classified into three clusters. Gene structure analysis revealed that StCLC genes contain 6–9 exons, and Motifs 6, 7, 8, and 9 were conserved across all seven StCLC proteins, suggesting their functional importance. Collinearity analysis indicated that the StCLC family has its own collinear genes and shares a close evolutionary relationship with the tomato (Solanum lycopersicum L) CLC family. GO annotation indicated that CLCs are primarily involved in chloride ion transport. Thirty-five cis-acting regulatory elements were identified in the promoter regions, predominantly associated with light response, abiotic stress, hormone regulation, and growth and development, implying potential roles in various physiological processes. RNA-seq data showed distinct expression patterns of StCLC genes across different tissues, indicating tissue-specific expression. Furthermore, qRT-PCR results demonstrated that under NaCl treatment, the expression levels of all seven StCLC genes, including StCLC3 and StCLC6, were significantly upregulated in roots, suggesting their active involvement in the response to salt stress.DiscussionThese findings elucidate the structural, evolutionary, and functional diversity of the StCLC gene family and highlight its important role in salt stress response, thereby providing a theoretical foundation for the genetic improvement of salt tolerance in potato.